Impact of Cultural Exposure and Message Framing on Oral Health Behavior: Exploring the Role of Message Memory. (October 2016) - Brick, Cameron; McCully, Scout N.; Updegraff, John A.; Ehret, Phillip J.; Areguin, Maira A.; Sherman, David K.
Background . Health messages are more effective when framed to be congruent with recipient characteristics, and health practitioners can strategically choose message features to promote adherence to recommended behaviors. We present exposure to US culture as a moderator of the impact of gain-frame versus loss-frame messages. Since US culture emphasizes individualism and approach orientation, greater cultural exposure was expected to predict improved patient choices and memory for gain-framed messages, whereas individuals with less exposure to US culture would show these advantages for loss-framed messages.Methods . 223 participants viewed a written oral health message in 1 of 3 randomized conditions—gain-frame, loss-frame, or no-message control—and were given 10 flosses. Cultural exposure was measured with the proportions of life spent and parents born in the US. At baseline and 1 week later, participants completed recall tests and reported recent flossing behavior.Results . Message frame and cultural exposure interacted to predict improved patient decisions (increased flossing) and memory maintenance for the health message over 1 week; for example, those with low cultural exposure who saw a loss-frame message flossed more. Incongruent messages led to the same flossing rates as no message. Memory retention did not explain the effect of message congruency on flossing.Limitations . Flossing behavior was self-reported. Cultural exposure may only have practical application in either highly individualistic or collectivistic countries.Conclusions . In health care settings where patients are urged to follow a behavior, asking basic demographic questions could allow medical practitioners to intentionally communicate in terms of gains or losses to improve patient decision making and treatment adherence.